Prevalence and indications for caesarean section in Enugu state, Nigeria - Nwoga, Hope O.; Ajuba, Miriam O.; Igweagu, Chukwuma P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Caesarean section (C/S) is one of the commonly performed surgical procedures in obstetrics. This procedure has been on the increase in the past decade, creating a public health concern. The objective of this study was to determine the prevalence and predictors of C/S delivery in a tertiary health facility in Nigeria. Methods: A prospective cohort study conducted at a tertiary health facility in Nigeria. Data was retrieved from the delivery cards of the mothers. Data was analysed using SPSS version 25 and variables were presented as frequencies, percentages, means, and standard deviation. Chi-square test was performed with the level of significance set at p≤0.05. Binary logistic regression was used to determine factors that predicted C/S delivery. Results: The prevalence of C/S was 48.3%. Commonest indication for C/S was 2 or more previous C/S. Mothers aged >30 years, employed, higher educational level, higher parity and delivered preterm predicted C/S delivery on logistic regression. Conclusions: The prevalence of C/S was high. Higher maternal age, employment, higher educational level, higher parity and preterm delivery were positively associated with C/S delivery.